Grindring the Self Young Filipino Gay Men's Exploration of Sexual Identity Through a Geo-Social Networking Application. [article]. - Castaneda, J.G.
The study investigated how young Filipino gay men use emergent technologies to explore their sexual identity. Incorporating research techniques from Sikolohiyang Pilipino, participants were asked to share their experiences of using Grindr, a geo-social networking application, and how it contributed to the way they understood and conceptualized what it meant to be a young Filipino gay man. Using frequency coding, the analysis revealed various themes based on data collected from 30 participants who did not use Grindr solely for its advertised purpose of finding partners for friendship and dating, or for its popular purpose of seeking sexual encounters. Results show that young Filipino gay men use the application to probe into personal issues relevant to their sexual identity. Themes include the desire to share one?s stories as a young gay man, to connect with whom they perceive to share similar experiences with, and to learn how to be gay. The implications of how emergent technologies such as geo-social networking applications can be understood as a space for exploring sexual identity are also discussed.
Keywords: Grindr; Geo-social networking application; Young Filipino gay men; Sexual identity; LGBT